Electronic medicine timer / Nurul Nur Nor Azmi, Raja Mohamad Syahmir Raja Mohsin and Wan Muhammad Syakir Wan Abdul Rahman - Nor Azmi, Nurul Nur; Raja Mohsin, Raja Mohamad Syahmir; Wan Abdul Rahman, Wan Muhammad Syakir (2015)
This project which is Electronic Medicine Timer is created for health and safety .This project was created for old people which has a chronic disease .This project was modify to make an easier medicine timer especially for old people. This project is easier to use and really low cost. Almost people can have their own electronic medicine timer. With this project more elder people can manage their life in getting medicine without forgot about it. This project was built which is suitable in any place.